Efficiency, Research, and Healthcare Economics: (Vital Threat Detection System) A Systematic Review - Review Afaf Aljuhani; Raghad Alraigi; Mashael Alotaibi; Nada Alamri; Salma Elhag (International Journal of Computers and Informatics, 2024)
Monitoring vital signs and detecting diseases like diabetes and cancer at an early stage are incredibly important for safeguarding patients’ lives and ensuring a healthy environment. In this study, we present a comprehensive systematic review focusing on vital monitoring systems in diverse fields. We reviewed 85 articles spanning from 2019 to 2024. From the selected articles, our aim is to explore the frameworks and algorithms of vital signs monitoring, the latest techniques used in remote vital signs monitoring such as radar and smart watch, as well as the measurement of vital signs for heart rate and respiratory diseases. Also, we discuss the threats that may affect healthcare systems and how to secure against these threats. The findings emphasize the critical importance of acquiring continuous vital monitoring systems, which have immense potential for improving healthcare. These systems are crucial for early diagnosis and prediction of conditions that may negatively impact the patient’s health. Additionally, it could be beneficial for doctors and healthcare staff by saving time and costs.